Ip Man 2 [videorecording (DVD)] : legend of the grandmaster - Ye, Weixin; Yen, Donnie, 1963-; Hung, Samo, 1952-; Hung, Samo, 1952-; Huang, Xiaoming, 1977-; Xiong, Dailin, 1981-; Yam, Simon (Well Go USA, 2010)
A new arrival in British-occupied Hong Kong wants to open a martial arts academy to teach his unique Wing Chun style. But a corrupt cabal of martial arts masters, led by Master Hung, refuses to allow him to teach in peace until he proves himself in a series of fights against the local master, which Ip does, in style. But even after earning the respect of the local masters, Ip's troubles are far from over.